2020
DOI: 10.1016/j.ijcha.2020.100662
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute coronary syndromes during the COVID-19 outbreak in Lombardy: The “macro-hub” experience

Abstract: Background During the COVID-19 outbreak, healthcare Authorities of Lombardy modified the regional network concerning time-dependent emergencies. Specifically, 13 Macro-Hubs were identified to deliver timely optimal care to patients with acute coronary syndromes (ACS). Aim of this paper is to present the results of this experience. Methods and Results This is a multicenter, observational study. A total of 953 patients were included, presenting with STEMI in 57.7% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Indeed, the lack of timely access to hospital care would be supported by the reported increase in the number of out-of-hospital cardiac arrest deaths 5 , 6 . Moreover, we observed an increase in-hospital mortality among STEMI patients in Lombardy, where the high prevalence of Covid-19 was associated with worse STEMI outcomes 7 . This could result from a delay in seeking hospital care by patients suffering a heart attack, which, in turn, would undermine the efficacy of a primary PTCA.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, the lack of timely access to hospital care would be supported by the reported increase in the number of out-of-hospital cardiac arrest deaths 5 , 6 . Moreover, we observed an increase in-hospital mortality among STEMI patients in Lombardy, where the high prevalence of Covid-19 was associated with worse STEMI outcomes 7 . This could result from a delay in seeking hospital care by patients suffering a heart attack, which, in turn, would undermine the efficacy of a primary PTCA.…”
Section: Discussionmentioning
confidence: 69%
“…There is the chance that patients with NSTEMI did not seek medical help because their symptoms were less frequently characterized by precordial pain or chest discomfort, thus increasing their reluctance to expose themselves to the in-hospital risk of COVID-19 infection. In line with this hypothesis, data from the Lombardy region in Italy showed that, during the COVID-19 pandemic, patients with AMI presented more frequently with dyspnea and atypical symptoms ( 40 ). In addition, an association between increasing age and pre-existing comorbidities and a poorer outcome following COVID-19 infection was largely emphasized by the media at the start of the pandemic, affecting the choice of some patients with NSTEMI to remain at home, since they considered themselves at high risk in case of infection due of their older age and concomitant illnesses.…”
Section: Clinical Characteristics and Outcomes Of Patients With Ami During Covid-19mentioning
confidence: 79%
“…An observation common to studies was that during the pandemic a higher percentage of patients were admitted with STEMI as compared to NSTEMI ( 25 , 28 , 40 ). Indeed, a large database of 99 English hospitals showed that, on average, hospitalization for NSTEMI was reduced by 50% and by 25% for STEMI ( 28 ).…”
Section: Clinical Characteristics and Outcomes Of Patients With Ami During Covid-19mentioning
confidence: 99%
“…Two of the main issues possibly related to that increase were the fear of in-hospital infection and the "surprise effect" of the pandemic on the healthcare systems, typical of the first pandemic wave [10]. It was unknown if information campaigns, adopted to increase citizens' awareness to call EMS in case of effected need, and re-organization of EMS and healthcare systems [28,29] may have prevented a similar increase during the second wave, avoiding the correlation between COVID-19 and OHCA incidence. Our study highlights that also in one of the first Region early affected by the pandemic, where the first case of COVID-19 in Europe was documented, and where multiple actions were adopted to mitigate the pandemic effect, an increase in OHCAs with a significant correlation between COVID-19 and OHCA incidence was observed also during the second pandemic wave, but only in high COVID-19 incidence provinces.…”
Section: Discussionmentioning
confidence: 99%